The use of high-intensity interval training (HIIT) in cardiac rehabilitation - a review - Barczewska, Magdalena; Bieszczad, Dominika; Reizer, Barbara; Botto, Zofia; Swojnóg, Marzena; Felisiak, Patrycja; Kowalczyk, Dominika; Śliwa, Zofia; Ślazyk, Dominik Andrzej; Krystek, Klaudia (Quality in Sport, 2025)
Background. Cardiac rehabilitation plays a crucial role in reducing mortality and improving the quality of life in patients after cardiovascular events. High-intensity interval training (HIIT) is gaining attention as a time-efficient and potentially more effective alternative to moderate-intensity continuous training (MICT). Aim. The aim of this review is to assess the effectiveness and the safety of high-intensity interval training in cardiac rehabilitation. Material and methods. A literature search was performed using PubMed database, narrowing it down to studies published between 2015 and 2025. The inclusion criteria focused on the use of high-intensity interval training in patients with coronary artery disease, after myocardial infarction, and with heart failure. Results. The analyzed studies demonstrated that high-intensity interval training significantly improves cardiorespiratory fitness, endothelial function, and metabolic parameters. Recent meta-analyses confirm the effectiveness of HIIT showing a significantly greater increase in peak oxygen uptake (VO₂ peak), with an average difference of approximately 1.42 mL/kg/min, compared to MICT. When patients are properly selected and monitored, HIIT is safe and well tolerated in cardiac rehabilitation programs. Conclusions. HIIT is an effective and safe form of exercise for cardiac patients and may complement or even replace traditional training approaches. However, it requires individualized programming and supervision by a specialized medical team. Further research is necessary to confirm its long-term outcomes.